2002
DOI: 10.1161/01.atv.0000014589.22121.6c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Intake on Measures of Lipid Metabolism Depends on Context Defined by Gender, Body Mass Index, Cigarette Smoking, andApolipoprotein EGenotype

Abstract: Abstract-Hyperlipidemia, smoking, and obesity are well-known risk factors for cardiovascular disease. Conversely, moderate alcohol intake is associated with lower atherosclerosis risk. However, the influence of taking alcohol on the interrelationships of these factors in a particular context has not been thoroughly investigated. In this study, we asked whether the association between plasma measures of lipid metabolism and alcohol intake is dependent on context defined by gender, age, body mass index (BMI), sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 35 publications
3
30
1
2
Order By: Relevance
“…Studies other than ours have also failed to find any effect of these factors on blood EPA and DHA levels (Ma et al, 1995). However, the decision was made to include BMI and smoking because of a potential effect of fat reservoirs and smoking on blood lipid levels (Wood et al, 1987;Bonaa et al, 1992;Lussier-Cacan et al, 2002), and sex because this factor, in combination with age, accounts for most of the inter-person variation in energy and nutrient intakes (Willett, 1990).…”
Section: Discussionmentioning
confidence: 89%
“…Studies other than ours have also failed to find any effect of these factors on blood EPA and DHA levels (Ma et al, 1995). However, the decision was made to include BMI and smoking because of a potential effect of fat reservoirs and smoking on blood lipid levels (Wood et al, 1987;Bonaa et al, 1992;Lussier-Cacan et al, 2002), and sex because this factor, in combination with age, accounts for most of the inter-person variation in energy and nutrient intakes (Willett, 1990).…”
Section: Discussionmentioning
confidence: 89%
“…The reasons for the sex difference in the association between alcohol intake and serum triglycerides are unclear and may simply be caused by confounding. However, differences in frequency of alcohol intake, 31 levels of sex hormone-binding globulin, 32 and genetic polymorphism in the apolipoprotein CIII, 33 apolipoprotein E, 34 and other factors controlling lipid metabolism may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Some population-based studies have also reported that e4 carriers are at increased risk for CVD (48). In contrast, only a few studies have reported pleiotropic effects of the six genotypes determined by the cSNPs at positions 3937 and 4075 on HDL-C and TG (13,32,37,49). The percentage of interindividual variation in HDL-C explained by these genotypes in a sample of Danish females is relatively small and depends on age (32).…”
Section: Lipid Phenotype-apoe Genotype Statistical Modelsmentioning
confidence: 99%
“…Studies of the influence of the variation in the gene coding for apolipoprotein E (APOE) on quantitative blood measures of lipid metabolism have demonstrated both context-dependent genotype effects (12)(13)(14) and phenotype-APOE genotype relationships that are less sensitive to contexts indexed by time and space (12,14,15). In the study reported here, we use data collected from three populations that are ethnically and geographically distinct to identify phenotype-APOE genotype relationships that are less sensitive to the influence of genetic and environmental contexts indexed by gender, ethnicity, and geographic location.…”
mentioning
confidence: 99%